Creation as Episteme of Transdiscipline Acmeology - Yevhen Palamarchuk; Vitaliy Mudrakov (Pedagogical Discourse, 2012)
The article deals with the characteristics and phenomenon of art's peculiarity. It determinates it's place and role as episteme of transdiscipline acmeology.